If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5 + -2i) + (-3 + 6i) = 0 Remove parenthesis around (5 + -2i) 5 + -2i + (-3 + 6i) = 0 Remove parenthesis around (-3 + 6i) 5 + -2i + -3 + 6i = 0 Reorder the terms: 5 + -3 + -2i + 6i = 0 Combine like terms: 5 + -3 = 2 2 + -2i + 6i = 0 Combine like terms: -2i + 6i = 4i 2 + 4i = 0 Solving 2 + 4i = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 4i = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 4i = 0 + -2 4i = 0 + -2 Combine like terms: 0 + -2 = -2 4i = -2 Divide each side by '4'. i = -0.5 Simplifying i = -0.5
| 1.2x+6.7=11.5 | | 12x=2x^2-7x+3 | | 12x+3=2x^2-7x+3 | | 4x+3-5x+2=11 | | z/10=-24 | | 3(x-4)÷4=1/2 | | 9.5x=x^2 | | (1+a)(1+b)=c | | 6x+6-4x=16-x | | -.22(-n+.33)=.22n-.55 | | -100+200= | | 1.66s=5+1.5-.25 | | (-1/2u^-3/2)(-2x) | | ln(x-3)=-8 | | 4/9=y-2:5 | | 1.66s=5 | | -100m+200m= | | 2(x+1)+3(x+5)=52 | | cos(1.6x)=0 | | 5x-3(4x-6)=-8 | | -2c-3x=-3 | | -4/13-8/13 | | 3x+5+6-10x+6= | | x+(x*0.15*14)=944 | | 7x+3-2x+1-4x=17 | | 3ln(4x+4)=20 | | -3=-9-2b | | -5x+15=-22 | | 5=-7-2a/3 | | 4x+5-x-1=34 | | 4x-11y-44=0 | | 3(x+9)-20= |